Potential of Peanut and Pumpkin-Based Biscuits for Dietary Management in Diabetes Mellitus Patients - Imanda Nurhaliza, Fadia Fadia; Kurniasih, Nunung (ISTEK, 2024)
People with type 2 diabetes mellitus often face challenges in achieving an adequate balanced diet that fulfills their nutritional needs. Pecans (Carya illinoinensis) are known to be rich in dietary fiber, protein, and healthy fats, and are a rich source of antioxidant polyphenols. Consumption of pecan nuts can help control blood sugar levels by lowering lipid levels and oxidative stress to improve insulin sensitivity in patients with type 2 diabetes mellitus. Therefore, this study aims to explore the potential of pecan nut biscuits as an alternative food that can help increase nutritional value and improve dietary management in patients with type 2 diabetes mellitus. The research methods used included biscuit recipe development, analysis of SNI No. 3571:2009, in vivo test of pecan nuts in male wistars, and nutritional analysis of raw materials. Pecan nut biscuits contain 35.0% carbohydrate, 12.7% protein and 33.1% lipid. Pecan nut biscuits are the most bioactive diet biscuits for patients with type 2 diabetes mellitus.